On the domain of analytic continuation of Lauricella–Saran’s hypergeometric functions $F_M$ and their ratios - Dmytryshyn, R.; Nyzhnyk, I. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We consider the problem of extending the Lauricella-Saran's hypergeometric functions $F_M$ by branched continued fractions. In three-dimensional complex space, the domain of analytical continuation of the Lauricella-Saran's hypergeometric functions $F_M$ and their ratios is established.